Enantioselective sulfoxidation reaction catalyzed by a G-quadruplex DNA metalloenzyme. Issue 62 (30th June 2016) - Cheng, Mingpan; Li, Yinghao; Zhou, Jun; Jia, Guoqing; Lu, Sheng-Mei; Yang, Yan; Li, Can
Abstract : Enantioselective sulfoxidation reaction is achieved for the first time by a human telomeric G-quadruplex DNA based biocatalyst. Abstract : Enantioselective sulfoxidation reaction is achieved for the first time by a DNA metalloenzyme assembled with the human telomeric G-quadruplex DNA and Cu(ii )–4, 4′-bimethyl-2, 2′-bipyridine complex, and the mixed G-quadruplex architectures are responsible for the catalytic enantioselectivity and activity.